The influence of anthropometric parameters in track and field curve sprint - Bonato, M.; Bizzozero, S.; Filipas, L.; La Torre, A. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Poor information is available regarding real field data on the different factors that could have an influence on curve sprint and its association with anthropometric and strength parameters. METHODS: We designed a crossover pilot-study that enrolled 14 track and field athletes of 200 and 400 m (8/14 men, age: 20.5±2.3 years, height: 1.73±0.06 m; body mass: 60.5±6.2 kg) that performed randomly in two different days assessment of anthropometric parameters, jump test by squat jump (SJ) and triple hop distance (THD), performance during a 20-m curve sprint (day 1), and assessment of 1RM for right and left limb on Bulgarian split squat (BSS) (day 2). The unpaired t test and Pearson`s correlation were used for data analysis. RESULTS: No statistical differences for anthropometric and strength parametric parameters between right and left lower limbs were observed. Twenty-meter curve sprints were negatively associated with body mass (P=0.0059, R=-0.7) and Body Mass Index (BMI; P=0.032, R=0.6). Moreover, a negative association was observed with SJ height (P=0.0025, R=-0.7), speed (P=0.0028; R=-0.7), strength (P=0.009, R=-0.7) and power (P=0.009, R=-0.7). Finally, 20-m curve sprint negatively correlated with right (P=0.0021, R=-0.7) and left (P<0.0001, R=-0.9) THD and 1 RM right (P=0.025, R=-0.6;) and left (P=0.0049, R=-0.7) BSS, respectively. CONCLUSIONS: This pilot study demonstrated that 20-m curve sprint was negatively associated with body mass, BMI, vertical jump performance, THD and 1RM BSS. This information could be useful to coaches and sport scientists as a reference value to improve athlete performance for 200- and 400-m athletes.